Empowering the Future: AI-Based Website Development Training to Boost High School Students' Creativity and Digital Skills - Luluk Muthoharoh; Yuliana Yuliana; Linda Rassiyanti; Ade Lailani; Ayu Sofia; Tiara Yulita; Dharu Cahyoaji Sasongko; Khairunnisa Maharani; Aditya Rahman (Smart Society, 2025)
In the rapidly evolving digital era, Artificial Intelligence (AI) has become one of the key technologies playing a significant role in various fields, including website development. AI-based website development training is a strategic step to enhance the skills and creativity of the younger generation in the era of digitalization. This activity was conducted at SMA Al Huda, South Lampung, with the aim of equipping students with an understanding of basic concepts, steps for creating websites, and how AI can be utilized to enhance creativity in the digital world. The methods used included interactive presentations, demonstrations, hands-on practice, and discussions. The activity also assessed students' knowledge before and after the training through an interactive quiz using Quizizz. The results of the study showed a significant improvement in students' understanding of AI-based website development. In conclusion, this training program was effective in enhancing students' skills and creativity in the digitalization world, particularly in creating AI-based websites